General Anesthesia vs. Local Anesthesia During Endovascular Treatment for Acute Large Vessel Occlusion: A Propensity Score-Matched Analysis - Han, Hongxing; Wang, Yu; Wang, Hao; Sun, Hongyang; Wang, Xianjun; Gong, Jian; Huo, Xiaochuan; Zhu, Qiyi; Che, Fengyuan (Frontiers in Neurology, 2022)
Objective To date, no consensus still exists on the anesthesia strategy of endovascular treatment (EVT) for acute ischemic stroke (AIS) due to large vessel occlusion (LVO). We aimed to compare the 90-day outcomes, puncture-to-recanalization time (PRT), successful recanalization rate, and symptomatic intracranial hemorrhage (sICH) of patients undergoing general anesthesia (GA) or local anesthesia (LA) ± conscious sedation (CS) during the procedure. Methods We selected patients from the Acute Ischemic Stroke Cooperation Group of Endovascular Treatment (ANGEL) registry and divided them into the GA group and the LA ± CS group. The two groups underwent 1:1 matching under propensity score matching (PSM) analysis. Then, we compared the primary outcome including the 90-day modified Rankin Scale (mRS) 0–2, secondary outcome including the 90-day mRS, the 90-day mRS 0–1, the 90-day mRS 0–3, PRT, and successful recanalization rate as well as the safety outcome including sICH, any ICH, and 90-day mRS 6. Results Among the 705 enrolled patients, 263 patients underwent GA and 442 patients underwent LA ± CS. After 1:1 PSM according to the baseline characteristics, each group has 216 patients. Patients with GA had the higher median 90-day mRS [3 (1–5) vs. 2 (1–4), p < 0.001], the lower 90-day mRS 0–2 rate (43.5 vs. 56.5%, p = 0.007), higher mortality (19.9 vs.10.2%, p = 0.005), and longer PRT [92 (60–140) vs. 70 (45–103) min, p < 0.001]. There were no differences in sICH and successful recanalization rate between both the groups. Conclusion In the real-world setting, LA ± CS might provide more outcomes benefits than GA in patients with AIS-LVO during the procedure.